If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + 15 = 4x + -9 Reorder the terms: 15 + 16x = 4x + -9 Reorder the terms: 15 + 16x = -9 + 4x Solving 15 + 16x = -9 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 15 + 16x + -4x = -9 + 4x + -4x Combine like terms: 16x + -4x = 12x 15 + 12x = -9 + 4x + -4x Combine like terms: 4x + -4x = 0 15 + 12x = -9 + 0 15 + 12x = -9 Add '-15' to each side of the equation. 15 + -15 + 12x = -9 + -15 Combine like terms: 15 + -15 = 0 0 + 12x = -9 + -15 12x = -9 + -15 Combine like terms: -9 + -15 = -24 12x = -24 Divide each side by '12'. x = -2 Simplifying x = -2
| 6y+1=61 | | -3x/4+1=7/12 | | 3x-3y=27 | | 3y+2y+y= | | x^2+xy+y^2=7 | | 8(1+w)=7(8+w) | | 5z-1=z+7 | | 7(x-3)-(6-2x)=-3x-2(5-x) | | 7x-11-4x=5x-8 | | 2msquared+1=19 | | (x+2)(x-2)=35 | | -4a+6+5a=15-22 | | 3x+2-3=8 | | -12/3(-8+(-4)^2-6)+2 | | 2m+1=19 | | 9x^3-36x^2+20x= | | 5/6x-1/2=-2 | | 16x-9=-8 | | 5(x+4)=9x+5-4x+15 | | 4-n=3n | | 6(z-6)-(9-5z)=10z | | 0=400-16t^2 | | 2x-(6y+2x)= | | 0.6(y-3)=0.1y | | 7z+10-5z=8+z+6 | | 3k/4=11/8 | | 20y-75=25 | | 0.4x-5=0.1(x+10) | | 6(y-5)=5y-4 | | 4/7x=-4 | | 2x-4(x-6)+5= | | 9.95+0.30(35)=c |